Protective Effects of Engineered Lactobacillus crispatus on Intrauterine Adhesions in Mice via Delivering CXCL12 - Kong, Yao; Liu, Zhaoxia; Xiao, Qin; Wu, Fei; Hu, Lijuan; Deng, Xiaorong; Chen, Tingtao (Frontiers in Immunology, 2022)
Endometrial injury is the main cause of intrauterine adhesions (IUA), and there are currently no effective prevention and treatment methods. Immune cells play an important role in damage repair by sensing changes in the microenvironment. Exogenous CXCL12 can promote tissue regeneration and repair by recruiting immune cells, but its effect and possible mechanism on endometrial regeneration and repair has not been reported. In the present study, we constructed an engineered Lactobacillus crispatus strain with pMG36e plasmid encoding CXCL12, and we developed two animal models, the intrauterine adhesion mice and the intrauterine adhesion mice with diabetes, and then evaluated the positive effects of this strain on the prevention of IUA after intrauterine surgery in normal and diabetic mice. The results indicate that treatment with L. crispatus-pMG36e-mCXCL12 strains significantly diminished the levels of pro-inflammatory factors interleukin-1β (IL-1β) and tumour necrosis factor-α (TNF-α) in serum and uterine tissues of IUA mice, with inhibition of the inflammatory (toll-like receptor 4/nuclear factor-κb, TLR4/NF-κB) and fibrotic (transforming growth factor-β1/smads, TGF-β1/Smads) signalling pathways in the uterine tissues. The high-throughput sequencing results further indicated that treatment with L. crispatus-pMG36e-mCXCL12 strains greatly increased the abundance of Lactobacillus spp. and reduced that of the pathogenic Klebsiella spp. in IUA mice. Furthermore, in the experimental group of intrauterine adhesion mice with diabetes, we obtained similar results to non-diabetic mice, that is, L.crispatus-pMG36e-mCXCL12 significantly improved fibrosis and inflammation in the uterine cavity of diabetic mice, and restored the vaginal microbiota balance in diabetic mice.Therefore, we speculated that vaginal administration of L. crispatus-pMG36e-mCXCL12 strains can effectively alleviate intrauterine adhesions by restoring the microbial balance and reducing inflammation and fibrosis caused by surgery.